Vibrio splendidus virulence in experimentaly challenged cod yolk sac larvae (Gadus morhua) - Ørstavik, Siri Frafjord (The University of Bergen, 2009)
Farming of Atlantic cod Gadus morhua, has become an important part of Norwegian aquaculture, but disease problems are frequent. Vibriosis caused by Vibrio splendidus has caused problems in aquaculture to early life stages of several marine species. It may also become a problem in cod hatcheries, as the bacterium is widely distributed in marine environments. The aim of the present study was to increase the understanding of V. splendidus infections in cod yolk sac larvae. Cod eggs were randomly selected from a single batch delivered by a commercial hatchery. Single eggs were transferred to wells in multi well dishes. Each well contained 2 ml of 80% aerated and sterile seawater. The eggs were challenged with 7 different strains of V. splendidus the same day as they arrived. The experiment did also include a negative control group consisting of unchallenged larvae and two positive control groups consisting of larvae challenged with two strains of Vibrio anguillarum. For each challenge strain 2 x 3 trays were put up (except for the negative control). Three trays were put up with a high dose, approximately 106 colony forming units (CFU) ml-1 and three trays were put up with a low dose 104 CFU ml-1. Two parallels were put up, one for mortality registration and one for immunohistological sampling. Presence of bacteria and pathological alterations were examined by immunohistochemistry. A total of 19 larvae from the negative control and 61 larvae from the challenged groups were investigated. No groups challenged with V. splendidus showed mortality significantly different from the negative control. Immunohistochemistry however, displayed positively stained bacteria in the intestine of the larvae as well as pathology. The bacteria could be observed in all lengths of the gastrointestinal (g.i) tract, but most findings were concentrated in the intestine. Two of the strains displayed higher amounts of bacteria in the intestine than the other groups. Pathology was observed mainly as shredded and necrotic cells in the stomach ...